Markets, Competition, Cooperation and Innovation. - Kitson, M; Michie, J; Sheehan-Quinn, M (Routledge, 2003)
The chapter analyses the relationship between, on the one hand, markets, competition and cooperation, and on the other hand, firms' innovative behaviour. The paper uses descriptive statistics and a qualitative response model to examine these relationships. Most firms face a relatively small number of major competitors. Non-price competition (or higher order qualitive competition) is ranked as more significant than price. We test formally for the relationships between competition, inter-firm cooperation and innovation. Our results indicate that a high level of domestic competition is positively correlated with the probability of innovating. In addition, inter-firm cooperation is found to be positively correlated with firms' probability of innovating. These results suggest that it is not just the degree of competition that is important but also the nature of the competitive process. Aspects of financial market pressure such as a take-over bid are found to be negatively correlated with the probability of innovating, especially in relation to product innovation.